Tackling Precarious Work in Public Supply Chains: A Comparison of Local Government Procurement Policies in Denmark, Germany and the UK. (June 2018) - Jaehrling, Karen; Johnson, Mathew; Larsen, Trine P; Refslund, Bjarke; Grimshaw, Damian
Through a cross-national comparative study of local government 'best practice cases' of socially responsible procurement in Denmark, Germany and the UK, this article critically examines the role of labour clauses in addressing issues of low wages and precarious work in public supply chains. It provides new insights on the negotiations and outcomes of labour clauses across different stages of the policy process, including implementation and monitoring. The analysis demonstrates the importance of pragmatic alliances of progressive local politicians, unions and employers in ensuring that socially responsible procurement moves beyond rhetoric, along with supportive national and sectoral employment regimes. Labour clauses can compensate for weak systems of labour market regulation by setting higher standards for outsourced workers, while they play a complementary role in more regulated labour markets by levelling up wages and working conditions to prevailing collectively agreed standards.